InAsSb photodiodes grown on GaAs substrates for long-wavelength-infrared gas-sensing applications. (23rd August 2021) - Fujita, H; Yasuda, D; Geka, H; Sakurai, Y; Kinoshita, K; Morohara, O; Suzuki, M; Shibata, Y; Kuze, N
Abstract: We investigated highly mismatched InAsSb photodiodes (PDs) grown on GaAs substrates working in the long-wavelength-infrared range (8–12 μ m). Because of their low absorption coefficient levels and high Auger recombination rates, InAsSb PDs suffer from several difficulties, including low responsivity and low resistance levels at room temperature. Additionally, the large lattice mismatch between the active layer and substrate material introduces a high density of dislocations and thus degrades performance. In the work described in this report, we realized high-performance InAs0.13 Sb0.87 PDs by reducing the density of dislocations as a result of applying a dislocation filter structure, as well as by optimizing interference within the active layer. The resulting device (cut-off wavelength of about 11 μ m) showed, at room temperature, a resistance R 0 of 90 kΩ and responsivity R i of 0.47 mA W −1 at a wavelength of 9.5 μ m, leading to a high detectivity D * of 1.2 × 10 8 cm Hz 1/2 W −1, which is suitable for detecting alcohol.